ESTIMATION OF BIOACCUMULATION, TRANSLOCATION AND DISTRIBUTION PATTERNS OF CADMIUM AND LEAD IN COMMONLY CONSUMED GREEN LEAFY VEGETABLES IN COLOMBO DISTRICT, SRI LANKA - Kananke, Thilini C; Wansapala, Jagath; Gunaratne, Anil (MATTER: International Journal of Science and Technology, 2018)
Green Leafy Vegetables (GLV) are a key component of the Sri Lankan diet. However, GLV are identified as good heavy metal accumulators, which in turns causes potential health risks for consumers through food chain contaminations. The present study aimed to investigate the bioaccumulation, translocation and distribution patterns of cadmium (Cd) and lead (Pb) in five key Sri Lankan GLV ["Kankun" (Ipomoea aquatica), “Mukunuwenna (Alternanthera sessilis), “Thampala” (Amaranthus viridis), “Nivithi” (Basella alba) and “Kohila” (Lasia spinosa)] grown in Colombo District, Sri Lanka. The levels of Cd and Pb in different plant parts (roots, stems and leaves) and the soil underneath were determined using the inductively coupled plasma optical emission spectroscopy (ICP-OES) and the bioaccumulation and translocation factors of heavy metals from soil to different plants parts (roots, stems, leaves), were calculated to identify the hyper accumulative species. Irrespective of the species and the location, GLV showed the distribution pattern for Cd and Pb as: roots>stems>leaves. In all the analyzed GLV, roots have accumulated significantly higher concentrations (at P<0.05) of Cd and Pb compared with stems and leaves. Among the two heavy metals, Cd bioavailability was higher compared with Pb. Amaranthus viridis had the lowest capacity for metal enrichment. In contrast, Lasia spinosa showed the highest bioaccumulation factors for both elements and the accumulation factor obtained for Cd (1.04) was >1. Thus, Lasia spinosa has the potential to use in phytoextraction purposes in future, though it is not safe to consume as a day to day food item.